Study and evaluation method of concrete erosion under a wind–sand flow load - Wei Liu; Yaoyu Zhu; Ying Jia; Jinyan Si; Li Zhu; Shucheng Li; Xueru Yang; Dangxian Xu (Case Studies in Construction Materials, 2025)
Many concrete buildings and infrastructures in sandstorm areas are subjected to years of sand and wind erosion. Wind erosion will damage the concrete, affect the structure durability, and even affect the safety of the structure in severe cases. In this paper, an experimental study of concrete erosion under the action of wind–sand two-phase erosion was carried out. The tests revealed the effects of wind speed, sand flux and sand particle size on wind erosion. The tests focused on the changes in the wind–sand flow pressure, wind erosion rate, strength loss rate, mass loss rate, and dynamic elastic modulus of the specimens. The wind erosion rate and dynamic elastic modulus degradation models were proposed. Based on the similarity principle, the corresponding transformation relationship between the actual erosion time under working conditions and the simulated erosion time during the tests was established. The results show that wind speed has the most significant impact on wind erosion. As the wind speed increases from 18 m/s to 30 m/s, the wind–sand flow pressure on the surface of the concrete specimen increases by 243.43 %, and the strength loss rate increases from 0.03 % to 9.34 %. The relative dynamic elastic modulus decreased from 65.26 % to 56.69 %. In addition, the digital images of the erosion-damaged concrete surface were statistically analysed in this study, and a method for evaluating wind erosion on the concrete surface based on digital images was proposed, which was verified to be reliable after tests.